A bibliometric analysis of the global branding literature and a research agenda - Chabowski, Brian R; Samiee, Saeed; Hult, G Tomas M (Journal of International Business Studies, 2013)
This study examines the citations used in the global branding literature (GBL), and evaluates the knowledge structure of this area of research to date. Our bibliometric analysis involves an examination of 120 global branding articles in business-related research. We employ multidimensional scaling to reveal a range of intellectual influences that have helped shape the GBL. The foundation of knowledge in the GBL is uncovered by analyzing co-citation data to identify important topical influences in the formation of global branding research. The conceptual framework developed incorporates five areas with important implications for the future development of global branding as an area of inquiry. These major research topics in the GBL are international branding strategy, brand positioning, brand/country origin, brand concept-image, and brand performance. We leverage resource- and capability-based paradigms, and use the five underpinning knowledge groups to propose an agenda for future research that fills existing gaps and offers the potential to advance and enrich the GBL.